EFEK SISA ASAM HUMAT DARI KOMPOS ALANG-ALANG DAN PENGELOLAAN AIR DALAM MENGURANGI KELARUTAN BESI (FE) PADA TANAH SAWAH BUKAAN BARU - Herviyanti Herviyanti; Gusnidar Gusnidar; Rina Alfina (Jurusan Tanah Fakultas Pertanian Universitas Andalas, 2007)
The research about residue effect of humic acid from imperata compost and water management to decrease the dissolved of iron (fe) on recently used ricefield had been conducted from march till august 2007. The objective is to study residue effect of humic acidity aplication and water management to controlling Fe and to increase rice production on recently used ricefield. The experiment using design factorial 2 x 4 with three replication wich is place as the split plot. The major factor is water management consisted of two treatment, thos were continously flooded (P1) and flooded and dried (intermittence) with two week interval (P2). The minor factor are four level from residue effect of humic acid (0, 200, 400, 600 ppm). The result of this study can provided the information that residue effect of humic acid at 600 ppm can reduce solubility of Fe2+ from 327,91 to 37,53 ppm for continously flooded and from 173,51 to 38,13 ppm for intermitten flooded. And the yield of rice (dry weight of 1000 grain ad straw) increase as much as 4,9 and 5,38 g with residue effect of humic acid at 600 ppm combination with intermittence flooded.Key word : humic acid, iron, recently used ricefield, intermittence, flooded.